The Role of Self-Confidence as a Mediator Influence of Family Social Support to Well-Being Patients of Stroke Patients - Sri Maryatmi, Anastasia (International Journal of Engineering and Technology, 2018)
In modern society stroke becomes a major threat in many countries. In Indonesia in 2015 stroke was ranked first as the cause of death. Stroke treatment takes a long time, and during that time the patient's physical and psychological condition will tend to decrease. In order to healing process to run optimally, the psychological aspects of the patient need more attention. One of that needs attention is the well-being, it is intended that the patient does not dissolve in his suffering. This study aims to examine the role of self-confidence as a mediator of the influence of family social support on the psychological well-being of patients with stroke. Respondents in this study were stroke patients who were undergoing therapy at three hospitals in Jakarta, amounting to 157 patients. Methods of data collection using a scale with Likert type. Based on the analysis of research data obtained results that family social support affects thepsychological well-being through self-confidence.Â